The Role of Social Media Tiktok to Interaction Social and Ethics in Generation Z - Nur Alya Sari Nasution; Mirda Khairunia; Ani Rahmadhini; Anita Kartika; Ifdhila Rahmi (Empowerment Counseling Journal, 2025)
This study aims to examine the role of TikTok social media on the social interactions and ethics of Generation Z, a generation born between 1997 and 2012 and very familiar with digital technology. The study used a qualitative approach with data collection techniques in the form of interviews, observations, and documentation. The results of the study show that TikTok is not only used as a medium for entertainment, but also an important space in building social identity, expressing oneself, and expanding social networks for Generation Z. This platform facilitates faster and more visual communication and encourages the formation of interest-based communities that strengthen digital interactions. However, the use of TikTok also brings ethical challenges, such as the spread of inappropriate content, pressure to follow viral trends, and the potential for blurring local cultural values. Some respondents showed ethical awareness in filtering content and maintaining personal values, but uneven digital literacy can be an obstacle. TikTok plays a role as a means of social and cultural transformation for Generation Z, but its use needs to be directed so as not to damage the existing social order and ethical values. This study emphasizes the importance of collaboration between users, educators, and platform providers to create a healthy and responsible digital ecosystem.